Strategi Pembelajaran Bahasa Arab dalam Meningkatkan Kemampuan Kognitif Peserta Didik - Nur Syahid (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2020)
Strategy is one thing that must be done in carrying out every action. Because by doing a strategy will get results in accordance with what will be achieved. Strategies in learning can increase motivation and effectiveness in learning so that in such situations and conditions learning strategies can make students gain both cognitive and intellectual abilities. This study aims to explain the Arabic language learning strategies that are carried out to improve students' cognitive abilities so that students are able to follow the lessons being implemented. The method in this research uses qualitative methods with descriptive analysis so that in this method the researcher will explain and analyze the learning strategies carried out. The results in this study indicate that an effective Arabic learning strategy is taught directly, followed by question practice and reading together so that in this learning process students will interact actively and will improve the existing cognitive system. In addition, students also train their self-confidence.